Healthy Eating Index-2015 and Predicted 10-Year Cardiovascular Disease Risk, as Well as Heart Age - Zhang, Yinyin; Lu, Cong; Li, Xinyu; Fan, Yameng; Li, Jiaqiao; Liu, Yamei; Yu, Yan; Zhou, Long (Frontiers in Nutrition, 2022)
Background and aims: Dietary factor plays an important role in the prevention of cardiovascular disease (CVD). The healthy eating index-2015(HEI-2015), an indicator of the overall dietary quality, has been introduced to reflect adherence to the 2015-2020 Dietary Guidelines for Americans (DGA). The present study aims to explore the associations of the HEI-2015 with predicted 10-year CVD risk and heart age among US adults aged 30-74 years old using data from the National Health and Nutrition Examination Survey (NHANES) 2011-2014. Methods and Results: We conducted a cross-sectional analysis among 6,614 participants aged 30-74 years old. The HEI-2015 scores were calculated from 2-days 24-hour dietary recall interviews. The 10-year CVD risk and heart age were derived from the sex-specific Framingham general cardiovascular disease risk score. We defined high cardiovascular disease risk as a predicted 10-year cardiovascular disease risk > 20%. Multiple linear regression and binary logistic regression models were used to investigate the associations of the HEI-2015 with predicted 10-year CVD risk and heart age. Compared with participants in the lowest HEI-2015 quartile, those in the highest quartile had lower predicted 10-year CVD risk (β=-2.37, 95% CI: -3.09--1.65, P<0.0001), lower heart age (β=-2.63, 95% CI: -3.29--1.96, P<0.0001) and lower odds for high risk of CVD (OR=0.62, 95% CI: 0.49-0.80, P-trend < 0.0001) after adjusting for multiple covariates. Conclusion: Higher adherence to the 2015-2020 Dietary Guidelines for Americans is associated with lower predicted 10-year cardiovascular disease risk and lower heart age among US adults.